Power Grid Information Leakage Prevention Technology Based on Service Calling Authentication Login Interface - Danhui LAI; Weifeng LUO; Jianhua HUANG; Xudong YUAN; Ziliang QIU (Zhongguo dianli)
In order to improve the security of power grid information, an anti leakage technology of power grid information based on service call authentication login interface is proposed. Build the information flow transmission path model, simulate the signal attack process, introduce the Markov chain method into the power grid steady state, quantify the risk of power grid information leakage, and design the terminal active immune structure. Simulation results show that the proposed method can reduce the number of information leakage, improve the efficiency and throughput of information encryption, and has the effect of preventing information leakage.